2003
DOI: 10.1177/120347540300700502
|View full text |Cite
|
Sign up to set email alerts
|

Valacyclovir in the Treatment of Herpes Simplex, Herpes Zoster, and other Viral Infections

Abstract: Valacyclovir is safe and effective in the therapy of patients with herpes simplex and herpes zoster and may be useful in other viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Wu et al. (11) reported that PHN was seen in 28% of patients. The incidence of PHN was similar to our result (24.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al. (11) reported that PHN was seen in 28% of patients. The incidence of PHN was similar to our result (24.7%).…”
Section: Discussionmentioning
confidence: 99%